Tailored synthesis of ultra-stable Au@Pd nanoflowers with enhanced catalytic properties using cellulose nanocrystals. (15th September 2022) - Abdul Hakkeem, Hasna M.; Babu, Aswathy; Shilpa, Nagaraju; Venugopal, Adithya A.; Mohamed, A.P.; Kurungot, Sreekumar; Pillai, Saju
Abstract: A green strategy for the synthesis of bimetallic core-shell Au@Pd nanoflowers (NFs) employing banana pseudo-stem-derived TEMPO-oxidized cellulose nanocrystals (TCNC) as both capping and shape-directing agent via seed-mediated method is presented. Flower-like nanostructures of Au@Pd bound to TEMPO-oxidized cellulose nanocrystals (TCNC-Au@Pd) were decorated on amino-functionalized graphene (NH2 -RGO) without losing their unique structure, allowing them to be deployed as an efficient, reusable and a green alternative heterogeneous catalyst. The decisive role of TCNC in the structural metamorphosis of nanoparticle morphology were inferred from the structural and morphology analyses. According to our study, the presence of –OH rich TCNC appears to play a pivotal role in the structured evolution of intricate nanostructure morphology. The feasibility of the bio-supported catalyst has been investigated in two concurrently prevalent model catalytic reactions, namely the oxygen reduction reaction (ORR) and the reduction of 4-nitrophenol, the best model reactions in fuel cell and industrial catalytic applications, respectively. Graphical abstract: Unlabelled Image